Developing Superplasticity in A AZ91 Magnesium Alloy Through a Combination of Rolling, ARB and ECAP - Greger, Miroslav; Zacek, David (Manufacturing Technology Journal, 2013)
The paper summarises results of experiments aimed at development of structure of modified Mg-Al-Zn alloys at hot deformation. Methods ARB and ECAP were used in the described experiment. It was proved that hardly forming materials could achieve very high plastics properties. After making plastics deformation, the using materials of alloy AZ91 analysed superplastics behaviour, it was certified by obtaining results, when ductility to rupture of alloy AZ91 was 418 %, it is demostrated at conclusion of the article. The experiment proved big influence of previous plastics deformation to ending values of mechanical properties. It was verified that better results are at rolling in more steps compared to rolling in one pass. The low submission temperature at last pass through die ,it causes obtaining higher final properties. It was obtained the material about grain size d ≍ 0.7 μm during using the technology of ECAP. Abreast of it the technology ARB enabled to get material of grain size in interval d ≍ 1-10 μm. The sekond technology brings higher strength properties. Only 3 cycles were sufficient to lower original grain size under limit 10 μm.
Keywords: magnesium alloys; ECAP; microstructure; mechanical properties; superplasticity